Qumran and the New Testament. - Frey, J. (Leuven : Peeters Publishers & Booksellers, 2024)
The volume Qumran and the New Testament comprises the papers read at the 71st meeting of the Colloquium Biblicum Lovaniense, which was held in 2022 to commemorate the 75th anniversary of the textual discoveries at Qumran, and reflects on the relevance of the scrolls for the understanding of the New Testament, now based on the knowledge of the complete Qumran corpus and recent research trends. The topics discussed in this volume go far beyond the previous habit of compiling parallels and the question of possible dependencies. They include sociological issues of comparable group identity, questions of halacha and liturgy, perspectives of performance criticism, and new historical insights into the growth of texts applied to the Synoptic tradition. Characterized by historical sobriety and caution, as well as hermeneutical awareness, the articles in this volume take the practice of textual comparison and the contextualization of the New Testament within the Scrolls to a promising new level.
Description based upon print version of record.
JSTOR
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Relation to the Old Testament; Dead Sea scrolls; Bible. -- Critique, interprétation, etc; Bible. -- Relation avec l'Ancien Testament; RELIGION / Biblical Studies / General; Electronic books